The Role of Artificial Intelligence on Employee Performance: A Literature Study - Haeruddin, M. Ikhwan Maulana (Southeast Asia Journal of Business, Accounting, and Entrepreneurship, 2025)
This literature review delves into the multifaceted impact of artificial intelligence (AI) on employee performance across a variety of sectors, including technology, healthcare, finance, and manufacturing. As organizations increasingly adopt AI technologies, understanding their implications becomes crucial for optimizing workforce effectiveness. The review investigates how AI enhances productivity by automating routine tasks, thereby freeing employees to engage in more strategic and creative activities. Furthermore, it explores the role of AI in improving decision-making processes by providing real-time data analytics, which enables employees to make informed choices that drive organizational success. In addition to productivity and decision-making, the review addresses the influence of AI on job satisfaction. By alleviating mundane workloads, AI fosters a more engaging work environment, contributing to higher employee morale and retention rates. However, the review also highlights the challenges associated with AI integration, such as potential job displacement, the skills gap, and ethical concerns regarding bias and privacy. By synthesizing findings from recent studies, this review not only provides insights into the evolving relationship between AI and human workforce dynamics but also identifies key themes, trends, and gaps in the existing literature. Ultimately, it offers a comprehensive understanding of AI's role in shaping employee performance, laying the groundwork for future research and practical applications in organizational settings.